Bauxite stabilization using gypsum and vermicompost against liquefaction in solid bulk cargoes - Muhammad Fat-Hi Al Juwaini, Pahrol (2020)
Liquefaction in solid bulk cargoes is a serious problem caused by granular cargoes such as crushed ore and minerals sands instability within aggregate. This study aim to stabilize bauxite using mixture of gypsum and vermicompost to reduce liquefaction risk in solid bulk cargoes. The method were initiated with factorial analysis in which the bauxites were amend by varies parameters such as percentage of gypsum, vermicompost, water intake and incubation days. The amendments undergo particle distribution and specific gravity test, the result from these test were then analyze for screening the main parameters that gives significant effect to both responses (particle distribution and specific gravity). The two main parameters (percentage of gypsum and vermicompost) that contribute most in the responses were study in central composite design where other two parameters (water intake of 50% and incubation days of 15 days) are remain fixed. Central composite design are important to narrowing and enhancing the initial value of preliminary analysis. At this stage, targeted value for the amendment to give optimal contributions were repeat for at least four times to ensure the variances are small. Targeted value for the mixtures to give optimal contributions (high value in 2.5 mm particle distribution) were then study in more details that includes aggregate stability (Le Bissonnais Method), flow table, particle distribution, specific gravity, scanning emission microscopy and energy dispersive x-ray. The data were analyze to produce the conclusive targeted value, which gives the optimal contribution. Analyses of 39 sample of amendment showed, at 6% of gypsum and 4% of vermicompost by weight is the optimal condition for increasing aggregate stability and significantly reduce liquefaction risk. Significantly improved its proportion of particle distribution at 2.5 mm by 20.38%, whereas in specific gravity, the amendments reduced by 20.67% which indicates the amount of 2.5 mm aggregate content in bauxite greatly reduced. Amendments also enhanced the erosion resistance of bauxite by 40% and the Mean Weight Diameter of amendment was recorded improvement by 75.51% when compare to unamend bauxite. In addition, flow table analysis showed that optimal amendment has higher Transportable Moisture Limit recorded at 26.97% when compare to natural moisture content, 24.07%. In the morphology studied, the combination of gypsum and vermicompost converted the aggregate from a sheet-like structure to a granular macro aggregated structure, whilst converting micro aggregates from a grain to a granular or prismatic structure. X-ray diffraction data shows that the amount of aluminum oxide not significantly affected by amendment made in this research. The findings of this work suggested that application of gypsum and vermicompost to bauxite directly influenced aggregate size distribution and its micromorphology, resulting in the improvement of aggregate stability to reduced liquefaction risk without changing its aluminum oxide content.